RAGAM PERSOALAN PENDIDIKAN DI INDONESIA DALAM TINJAUAN KRITIS FILSAFAT PENDIDIKAN - Gede Agus Siswadi (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2023)
Humans in their lives need education to develop all the competencies they have. So that the role of education is very vital in human life. Education is also often referred to as a human effort to free oneself from ignorance. However, behind the important role of education, there are actually various educational problems that have hindered various aspects of human development. This research seeks to look at various problems in education through qualitative methods with a phenomenological approach. The results of this study indicate that there is still capitalism in education, then the practice of dehumanization, education which should be a humanist institution but there is a phenomenon of violence in education. Policies in education are also changing which indicates where the direction of education in Indonesia is becoming unclear. Elitism and castelism in education also occur, which causes unequal access to education. Furthermore, education requires philosophy to solve various problems in education that cannot be solved by educational science. The importance of learning in the 21st century to use technology in education. Keywords: Dishumanization, Capitalism, Castanization, Educational Philosophy.